2013
DOI: 10.1007/s10633-013-9420-z
|View full text |Cite
|
Sign up to set email alerts
|

Disease progression in autosomal dominant cone–rod dystrophy caused by a novel mutation (D100G) in the GUCA1A gene

Abstract: Purpose To document longitudinal fundus autofluorescence (FAF) and electroretinogram (ERG) findings in a family with cone-rod dystrophy (CRD) caused by a novel missense mutation (D100G) in the GUCA1A gene. Methods Observational case series. Results Three family members 26 to 49 years old underwent complete clinical examinations. In all patients, funduscopic findings showed intraretinal pigment migration, loss of neurosensory retinal pigment epithelium (RPE), and macular atrophy. Fundus autofluorescence (FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…4 and Supplementary Tables T1-T3 ). The dynamic analysis performed with PyInteraph highlighted the constant presence of D64 and D100 among the highest-degree hubs, a particularly important result since D100 is the target of the cone-dystrophy related D100E/G mutations 17 41 . Other residues target of retinal dystrophy-associated point mutations were found among high-degree hubs both in the GC activating and inhibiting states of mGCAP1 and, to a lower extent, of nmGCAP1 ( Supplementary Tables T1 and T2).…”
Section: Discussionmentioning
confidence: 99%
“…4 and Supplementary Tables T1-T3 ). The dynamic analysis performed with PyInteraph highlighted the constant presence of D64 and D100 among the highest-degree hubs, a particularly important result since D100 is the target of the cone-dystrophy related D100E/G mutations 17 41 . Other residues target of retinal dystrophy-associated point mutations were found among high-degree hubs both in the GC activating and inhibiting states of mGCAP1 and, to a lower extent, of nmGCAP1 ( Supplementary Tables T1 and T2).…”
Section: Discussionmentioning
confidence: 99%
“…When the 30 Hz-flicker amplitudes were lower than five microvolts or predicted to be lower than five microvolts based on exam, Burian-Allen contact lens electrodes were used to record the 30 Hz-flicker responses that are subsequently processed through narrow band-passed filtering with computed averaging 26 , 44 , 46 , 47 . The amplitudes obtained from both eyes were measured by a single user with Espion V6.0.56 software (Diagnosys LLC, Lowell, MA, USA), which calculates the amplitude from trough to peak of the first visible waveform, as performed previously 46 , 48 50 . Amplitudes of both eyes were averaged and compared between the two groups.…”
Section: Methodsmentioning
confidence: 99%
“…Mutations in GUCA1A, encoding for GCAP1 result in aberrant GC regulation and in retinal degeneration, a set of progressive diseases involving cones, the macula, and in some cases rods, ultimately leading to blindness [11][12][13]. To date, 20 GCAP1 variants have been associated with retinal dystrophy [14][15][16][17][18][19][20][21][22][23][24][25], with one of the most recently discovered being the G86R mutation, located in the previously mentioned hinge region [26]. Biochemical experiments performed with the GC-GCAP1 reconstituted system in the presence of the G86R mutation showed that the complex forms with higher affinity than the WT and it is unable to decelerate the GC at high Ca 2+ -levels corresponding to the dark-adapted state [26].…”
Section: Introductionmentioning
confidence: 99%